PELATIHAN HALAL BERBASIS SINERGI AKADEMISI DENGAN INDUSTRI SEBAGAI STRATEGI PEMBERDAYAAN MASYARAKAT - Faizatul Fitria; Umul Farida; Nurul Istiqomah; Reza Alrayan; Endro Puji Astoko (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
Halal training is a community empowerment strategy aimed at increasing the capacity of MSMEs/SMIs to understand the halal concept, certification process, and the application of halal standards in product production and branding. This activity was implemented using a participatory and collaborative approach between academia and industry, involving 30 participants in Kediri Regency. The training method included needs analysis, interactive lectures, technical practice, and evaluation through pre- and post-tests. The evaluation results showed a significant increase in participant understanding, with the high category increasing from 19.35% to 60.48%. Cross-sector collaboration has proven effective in bridging theory and practice, accelerating the halal certification process, and strengthening halal business networks at the local level. This activity contributes to the achievement of sustainable development goals, particularly in the aspects of responsible consumption and production. In addition, this training has had a tangible impact in the form of increased consumer trust in MSME products. The success of this program demonstrates that the integration of academia and industry can be a sustainable model for the development of the halal ecosystem in Indonesia.